REKAYASA PERANGKAT LUNAK PENJUALAN PULSA ELECTRIC BERBASIS SMS MENGGUNAKAN VISUAL BASIC 6.0 - Eva Yulianti; Tauvan Rusyiatno (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2013)
Expansion of information technology through computers in all fields requiring a better handling, the counter emerging issues such as the fiesta Communica-checking balances and the amount and cost of media required for the supply of blank-blank and report of the transaction process. Therefore, to facilitate the transaction "Fiesta Communications' want to create a system that can facilitate both the sale and purchase transactions. To that end, the author makes a system that is really needed or in accordance with the desires of the counter "Communica Fiesta '. manufacturing applications using Visual Basic 6.0, MySQL, Navicat. and a software interface such as Mobile FBUS ActiveX 1.5. To make this application first author conducted the analysis consists of the old systems analysis, user needs analysis and feasibility analysis of the system. Application of pulse sales system makes it easy for owners counter "Communica Fiesta" in terms of checking balances, sales report creation and recording of purchase and sale transactions .